Peran Pendidikan Agama Islam dalam Meningkatkan Daya Tahan Budaya Lokal Indonesia di Era Global - Ali, Muhammad; Surti, Mayang; Wahyudi, Dedi (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2019)
There is a significant relationship between modernization and religion in this modern and global era. In the Indonesian context, religion, teaching patterns and traditions, are preserved as a fundamental basis for morality to influence the flow of modernization. Indonesian society, in general, is divided into two modernist and traditional groups. This grouping occurs because of the historical perspective. The existence of Islam in Indonesia collides with various forms of local syncretism and also with Western civilization, especially in the period of colonialism and traditions of ancestors. As happened in the Javanese tribe, they still perform traditional ceremonies, as well as in other regions in Indonesia. This study reveals the role of Islamic education in enhancing the resilience of local culture in Indonesia to remain consistent despite being hit by currents of modernization and globalization.